WORKING ON THE BASIS OF MATHEMATICS TEACHING METHODS - Mamarakhimova Hulkar Nizomovna (The Conference Hub, 2025)
Elementary mathematics is also a subject with an independent content, which is built on the basis of elementary information obtained from various branches of higher mathematics, namely theoretical arithmetic, number theory, higher algebra, mathematical analysis and the logical course of geometry.
Keywords: Mathematics, methodology, general methodology, special methodology, general educational goal, educational goal, practical goal